Induksi Teknologi Budikdamber (Budidaya Ikan Dalam Ember) Untuk Rumah Pangan Generasi Milenial - Pramudia, Zulkisam; Moehammad, Khibar Syiar; Susanti, Yogita Ayu Dwi; Dewi, Citra Satrya Utama; Dailami , Muhammad; Gafur, Abdul (Penerbit Goodwood, 2025)
Purpose: The 1000 Villages Strategic Service Activity aims at community service activities with this strategic service scheme to introduce household-scale cultivation technology, namely Budikdamber, for millennial generation food houses to support increased food security in Bondowoso Regency. Methodology/approach: This service was carried out in Bondowoso Regency Maes an. These locations are at SMK Negeri 1 Maesan, and the Az Zahra Mosque Youth Secretariat, Pekingan Village. The method for implementing Strategic Service Grant activities is designed using a participatory approach, where both the activity implementer (UB) and the recipient (target partner) are proactive in carrying out service activities. Results/findings: The parameter for success is that the millennial generation has succeeded in increasing their knowledge and practice of fish cultivation through induction of Budikdamber technology, assistance with the Budikdamber system to increase analytical skills in cultivating aquaponic systems, and the process of mentoring water quality management. Conclusion: The community service program was successfully implemented by partner participants as a household-scale aquaculture solution. Its success was demonstrated through their understanding of water quality management based on CBIB principles. Limitations: The study cultivating aquaponic systems, and the process of mentoring water quality management. Contribution: This community service activity is the induction of household-scale aquaculture technology, namely Budikdamber, for millennial home-based food systems to support improved food security in Bondowoso Regency, which was successfully implemented and carried out by the partners.